The Impact of Social Media Marketing on TikTok: Exploring Brand Awareness and Consumer Brand Engagement as Mediators of Purchase Intention among Gen Z in Padang: Pengaruh Social Media Marketing pada Aplikasi TikTok terhadap Purchase Intention dengan Brand Awareness dan Consumer Brand Engagement sebagai Variabel Mediasi pada Gen Z di Kota Padang - Erin Rahayu Fernanda; Vidyarini Dwita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Social Media Marketing (SMM) has become a pivotal strategy in influencing consumer behavior, particularly among Gen Z, who are active TikTok users. This study investigates the impact of SMM on purchase intention (PI), mediated by brand awareness (BA) and consumer brand engagement (CBE). Using a quantitative approach, data were collected from 200 Gen Z respondents in Padang, Indonesia, through purposive sampling. The results reveal significant relationships between SMM, BA, CBE, and PI. Notably, BA and CBE mediate the relationship between SMM and PI, underscoring the importance of these variables in enhancing marketing effectiveness. The findings provide practical insights for marketers aiming to optimize their TikTok strategies.